Ask the Locals: A Community-Informed Analysis of Perceived Marine Environment Quality Over Time in Palawan, Philippines - Sumeldan, Joel D. C.; Richter, Isabell; Avillanosa, Arlene L.; Bacosa, Hernando P.; Creencia, Lota A.; Pahl, Sabine (Frontiers in Psychology, 2021)
Despite the potentially huge contributions that coastal communities might make in marine resource management and sustainability, their participation in such efforts have only been recognized recently, particularly in Southeast Asia. Involving community perceptions can offer new insights for policy makers and resource managers and can elicit strong commitment and support from the communities themselves. This paper aims to understand perceptions of coastal communities of local environmental issues, specifically how these have developed over time, to understand expectations and perceptions of trends. Sixteen marine environmental issues were identified during stakeholder meetings in Palawan, Philippines. A co-developed survey was administered to 431 respondents from coastal communities in two municipalities (Taytay and Aborlan) and the city of Puerto Princesa in Palawan. The results show variation in perceptions and expectations between issues. We find that communities expect positive trends for mangrove-, beach tree- and sea grass coverage as well as for seaweed farming and drinking water quality. The amount of plastic litter, wild fish and shellfish, and the severity of sewage pollution is perceived to get worse. The aquaculture sector is expected to remain unchanged in the future as it has been in the past. We also find significant differences in how people from different areas of residence perceive their marine environment. In the discussion, we mapped these different community perceptions on existing policies and their implementation. We further recommend how community perceptions can be integrated into resource management and policy making in the future.